Improving the logistics process at the company's warehouses - Long, Hui (Харківський національний автомобільно-дорожній університет, 2024)
The relevance of the problem under consideration is determined by the fact that the market strategy of economic formation provides for the balanced development of all sectors of the national economy - both material production and infrastructure. The paper considers the theoretical aspects of organization and improvement of warehousing at an enterprise; analyzes and evaluates the functioning of the logistics process in warehouses; identifies the shortcomings existing in the warehousing of an enterprise; develops measures to improve the logistics process in the warehouses of an enterprise; and evaluates the economic efficiency of the proposed measures.
Keywords: logistics; types of logistics activities; warehouse logistics; production stocks; material flows